Meconium Aspiration Syndrome in Neonates (Medical Forum Monthly, 2024)
Objective: To determine the frequency of the factors leading to meconium aspiration syndrome in neonates.Study Design: Descriptive case series study.Place and Duration of Study: This study was conducted at the Neonatal Unit of the Department of Pediatric Medicine, Sheikh Zaid Postgraduate Medical Institute Lahore from 02-08-2013 to 2-02-2014Materials and Methods: A total of 180 patients were selected for this study. After verbal consent for participating in the study mothers were inquired for factors leading to meconium aspiration syndrome like post maturity and cesarean section with detailed history including date of last menstrual period and mode of delivery and filled in predesigned proforma. Results: There were 101 (56.1%) male and 79 (43.9%) female patients. Neonates delivered with cesarean section were 73 (40.6%), 85 (47.2%) patients had post maturity and 7 (3.9%) patients had IUGR. There were 13 (7.2%) patients had pneumothorax and mortality was recorded in 8 (4.4%) patients.Conclusion: Cesarean section, post maturity and IUGR are important risk factors, frequently associated with meconium aspiration syndrome.